Executive and non-executive auditors and environmental disclosure among listed firms in Nigeria - Yunusa, N.; Mohamed, Rapiah; Che Adam, Noriah (Akademia Baru, 2016)
This study confirmed the relationship between executive and non-executive auditors in relation to environmental disclosure among the annual reports of environmentally sensitive listed companies in Nigeria.This is in line with the objective of this research that is to examine empirically the role of executive and non-executive auditors on the environmental disclosures of environmentally sensitive listed companies in Nigeria.The data of the study is collected from the financial annual reports of the said listed companies during as at 31st December, 2014.The dependent variable environmental disclosure is derived from the Global Reporting Initiative checklist while the executive and non-executive auditors are the number of executive and non-executive auditors in the audit committee of the company respectively.Using ordinary least square regression to test the hypothesis of the study however, the result of the study shows that while executive auditors have no significant relationship with environmental disclosure, non-executive auditors is found to be positively significant impacted on environmental disclosure in Nigerian environmentally sensitive listed industries.